Tua Korhonen and Erika Ruonakoski. Human and Animal in Ancient Greece: Empathy and Encounter in Classical Literature. - Kindt, Julia (Journal of Greek Archaeology, 2018)
Can a firm line be drawn between man and beast? If so, on what grounds? And what distinguishing feature sets man apart from all other creatures? These questions, summarized in the so-called ‘question of the animal’, features prominently in philosophical debates throughout antiquity. In particular, Aristotle and the Stoics made the case for a strong dividing line that separates man from animal, invoking numerous human attributes – speech, reason, justice, morality, to name just a few – that are allegedly specific to man and man only (see in detail Sorabji).